The Effect of Moringa oleifera Leaf Extract Administration through Drinking Water on Liver Weight, Gizzard Weight, Small Intestine Weight, and Small Intestine Length in Broiler Chickens - Mesah, Petwel Dedenuari; Mulyantini, Ni Gusti Ayu; Suryatni, Ni Putu F.; Ndun, Alberth Nugrahadi (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
This study aimed to examine the effect of Moringa oleifera leaf extract administered through drinking water on liver weight, gizzard weight, small intestine weight, and small intestine length in broiler chickens. The research was conducted at the Poultry Workshop Facility of the Faculty of Animal Husbandry, Marine and Fisheries, Universitas Nusa Cendana, Kupang, from April 7 to May 26, 2023. The experimental design was a Completely Randomized Design (CRD) with four treatments and six replicates, each replicate consisting of four chickens. In total, 96 broiler chickens were used in the study. The treatments were as follows: P0: drinking water without Moringa leaf extract, P1: drinking water + 40 mL/L Moringa leaf extract, P2: drinking water + 80 mL/L Moringa leaf extract, and P3: drinking water + 120 mL/L Moringa leaf extract. The parameters measured included liver weight, gizzard weight, small intestine weight, and small intestine length. Statistical analysis results indicated that all treatments showed no significant differences (P>0.05) in liver weight, gizzard weight, small intestine weight, or small intestine length. The study concluded that the administration of Moringa oleifera leaf extract through drinking water had no effect on the liver weight, gizzard weight, small intestine weight, or small intestine length of broiler chickens.